Analisis Family-Type Board Game Menggunakan Kerangka MDA Untuk Perancangan Media Pengenalan Desain Produk - Claritza Nathania Setiadi; Guguh Sujatmiko; Hedi Cintya (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2026)
The product designer profession plays an important role in the creative industry; however, interest among younger generations remains relatively low. An engaging and accessible medium is needed to introduce the complexity of this profession to high school students. This study analyzes family-type board games using the MDA (Mechanics, Dynamics, Aesthetics) framework as a foundation for designing an introductory educational medium for product design. A qualitative approach was employed through observational analysis of occupation-themed board games. The study identifies mechanics, dynamics, and aesthetic during gameplay. The findings indicate that resource management and progressive development mechanics effectively simulate real-world work processes. Dynamics such as action planning and resource counting foster strategic decision-making, while strong thematic integration enhances immersion and supports understanding of the represented profession. These findings provide a conceptual basis for designing board games as educational media to introduce the product designer profession to high school students.